THE PROSPECT OF INTEGRATED AND HOLISTIC MADRASAH EDUCATION SYSTEM (IHMES) IN THE PHILIPPINES: A Sustainable Approach to Prevent Violent Extremism - Cayamodin, Jamel Rombo (TARBIYA: Journal of Education in Muslim Society, 2019)
ABSTRACTThe madrasah education system in the Philippines was recently impugned as a source of radicalized Muslim Filipino youths. This assertion was based on the presumption that most radicalized youths who happened to be members of either the revolutionary groups or the ISIS-inspired groups went through the diverse madrasah institutions in the country. This indictment, however, may be parti pris to the substantial majority of Muslim Filipino youths who served the nation in various capacities as also a product of various madrasah institutions in the Philippines and abroad. More vividly, many of the highly educated Muslim Filipino youths are actively engaged in various government and non-government programs on preventing and countering violent extremism. These two opposing views made the examination of the dynamics of the Philippine madrasah education system imperative to vindicate the issue. Using analysis of documents, the study found that there are challenges and gaps in the implementation of the madrasah programs even though it is mandated by existing legislations, policies, and peace agreements. Thus, a sustainable integrated and holistic madrasah education system (IHMES) acquiescent to the religio-cultural orientations of Muslim Filipinos is proposed to empower Muslim communities, eliminate various social ills particularly violent extremism, and meaningfully participate in nation-building.  ABSTRAKSistem pendidikan madrasah di Filipina akhir-akhir ini dibantah telah menjadi sumber bagi radikalisasi pemuda Muslim Filipina. Pernyataan ini didasari pada dugaan bahwa generasi muda yang paling banyak terpapar radikalisme dan menjadi anggota grup revolusioner ataupun grup yang terinspirasi oleh ISIS menempuh pendidikan di berbagai institusi madrasah di negara tersebut. Meski begitu, dakwaan ini mungkin saja merupakan prasangka atas adanya mayoritas pemuda Muslim Filipina yang bekerja dalam melayani negara di bergagay bidang yang juga merupakan lulusan dari institusi-institusi madrasah, baik di dalam maupun luar Filipina. Lebih jelasnya lagi, kebanyakan pemuda Muslim Filipina yang berpendidikan tinggi berperan aftif dalam berbagai program, baik yang diadakan oleh pemerintah maupun swasta dalam rangka menangkal dan melawan ekstrimisme dan kekerasan. Kedua pandangan yang menentang ini membuat pemeriksaan dinamika sistem pendidikan madrasah Filipina sangatlah penting, demi membuktikan kebenaran kasus ini. Dengan menggunakan analisis terhadap dokumen yang ada, studi ini pun menemukan fakta bahwa terdapat tantangan dan kesenjangan dalam penerapan program madrasah, meskipun mereka telah berada di bawah pengawasan perundang-undangan yang ada, kebijakan, dan juga perjanjian kedamaian. Oleh karenanya, sebuah sistem pendidikan madrasah yang terintegrasi dan holistik yang berkelanjutan (integrated dan holistic madrasah education system, IHMES) sepakat pada orientasi agama-budaya Muslim Filipina agar dapat diajukan, hal tersebut betujuan dilakukannya pemberdayaaan komunitas Muslim demi menyingkirkan berbagai penyakit sosial, terutama ekstrimisme kekerasan, dan yang juga berarti sebuah partisipasi dalam membangun negara.